Silver nanoparticles with excellent biocompatibility block pseudotyped SARS-CoV-2 in the presence of lung surfactant - Gupta, Govind; Hamawandi, Bejan; Sheward, Daniel J.; Murrell, Ben; Hanke, Leo; McInerney, Gerald; Blosi, Magda; Costa, Anna L.; Toprak, Muhammet S.; Fadeel, Bengt (Frontiers in Bioengineering and Biotechnology, 2022)
Silver (Ag) is known to possess antimicrobial properties which is commonly attributed to soluble Ag ions. Here, we showed that Ag nanoparticles (NPs) potently inhibited SARS-CoV-2 infection using two different pseudovirus neutralization assays. We also evaluated a set of Ag NPs of different sizes with varying surface properties, including polyvinylpyrrolidone (PVP)-coated and poly(ethylene glycol) (PEG)-modified Ag NPs, and found that only the bare (unmodified) NPs were able to prevent virus infection. For comparison, TiO2 NPs failed to intercept the virus. Proteins and lipids may adsorb to nanoparticles forming a so-called bio-corona; however, Ag NPs pre-incubated with pulmonary surfactant retained their ability to block virus infection in the present model. Furthermore, the secondary structure of the spike protein of SARS-CoV-2 was perturbed by the Ag NPs, but not by the ionic control (AgNO3) nor by the TiO2 NPs. Finally, Ag NPs were shown to be non-cytotoxic towards the human lung epithelial cell line BEAS-2B and this was confirmed by using primary human nasal epithelial cells. These results further support that Ag NPs may find use as anti-viral agents.